Earth Plasters - Lima, José (2022)
Earth-based mortars have been used all over the world since ancient times in an extensive range of building types from vernacular architecture to monuments. Plastering is one of the most common contemporary applications of earth-based mortars used for earthen-building conservation or modern architecture. Raw earth is a very diverse natural material, and clay minerals play a key role in plaster properties being responsible for their setting process and providing the capacity of balancing the indoor hygrometric conditions of buildings. This capacity offers significant benefits to energy savings delivering comfort and health of inhabitants and also contributes to building conservation. For this study, three mortars were produced with different clayish earths to assess the influence of clay mineralogy. Mortars characterization confirmed that clay mineralogy drives important plaster properties, such as vapour adsorption and drying shrinkage, while also having a significant influence on mechanical strength, dry abrasion, and thermal conductivity. Within the studied mortars, illitic clayish earth stands outs as more adequate for earth-based plasters, showing balanced properties, namely linear drying shrinkage, mechanical strength, dry abrasion, and water vapour adsorption.